2019
DOI: 10.1177/1545968319886444
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in Stroke Rehabilitation and Recovery Research: Consensus-Based Core Recommendations From the Second Stroke Recovery and Rehabilitation Roundtable

Abstract: Cognitive impairment is an important target for rehabilitation as it is common following stroke, is associated with reduced quality of life and interferes with motor and other types of recovery interventions. Cognitive function following stroke was identified as an important, but relatively neglected area during the first Stroke Recovery and Rehabilitation Roundtable (SRRR I), leading to a Cognition Working Group being convened as part of SRRR II. There is currently insufficient evidence to build consensus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…One of the challenges in advancing research on cognitive impairment post-stroke is to establish and validate test platforms that allow for parallel cognitive assessments in humans and animals in experimental models of stroke 5 . This was recently reiterated in the core recommendations from the recent second Stroke Recovery and Rehabilitation Roundtable 6 .…”
Section: Introductionmentioning
confidence: 93%
“…One of the challenges in advancing research on cognitive impairment post-stroke is to establish and validate test platforms that allow for parallel cognitive assessments in humans and animals in experimental models of stroke 5 . This was recently reiterated in the core recommendations from the recent second Stroke Recovery and Rehabilitation Roundtable 6 .…”
Section: Introductionmentioning
confidence: 93%
“…This research demonstrated how the PRPP can be applied to a broad range of tasks and performed by stroke survivors receiving ESD without increasing the assessment load on patients or therapists. It is imperative that assessments are easily implemented in multiple settings, valid for a broad client base and examine executive function (McDonald et al, 2019). In this study, each tool was scored in full, suggesting that these tools have clinical utility in ESD.…”
Section: Discussionmentioning
confidence: 88%
“…Cognitive impairment is a common and significant sequela post stroke, adversely affecting independence in activities of daily living (ADL), instrumental activities of daily living (IADL) (Intercollegiate Stroke Working Party (ISWP), 2016: 53) and quality of life (McDonald et al, 2019). It is essential that stroke survivors receive screening for post-stroke cognitive impairment with standardised tools and, when indicated, a thorough cognitive assessment to guide intervention (ISWP, 2016: 59).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these setbacks, researchers are continuously developing new methods and refining models, as well as investigating novel avenues of research that hold significant promise in improving stroke outcome ( Silasi et al, 2015 ; Gouveia et al, 2017 ; Kannangara et al, 2018 ; Freitas-Andrade et al, 2019 ; Hill et al, 2020 ; Mendonca et al, 2020 ; Rayasam et al, 2020 ; Zhang et al, 2020 ). A greater appreciation for the role of physical rehabilitation and insight into the molecular mechanisms at play has led to a significant impact on the quality of life after stroke ( Fang et al, 2019 ; McDonald et al, 2019 ; Sun and Zehr, 2019 ).…”
Section: Discussionmentioning
confidence: 99%